2023
DOI: 10.1002/cam4.5760
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of cognitive interventions for adult patients with brain tumours

Abstract: Background: Neurocognitive impairments are common in patients with current or previously treated brain tumours, and such impairments can negatively affect patient outcomes including quality of life and survival. This systematic review aimed to identify and describe interventions used to ameliorate (improve) or prevent cognitive impairments in adults with brain tumours. Methods: We performed a literature search of the Ovid MEDLINE, PsychINFO and PsycTESTS databases from commencement until September 2021. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
(452 reference statements)
0
8
0
Order By: Relevance
“…The inclusion of more people with glioma may have provided a greater diversity of views. However, recruiting people with glioma was challenging, partly due to the effects of the COVID-19 pandemic, and also reflects the small sample sizes seen in other studies with this patient group ( Kirkman et al, 2023 ). Most participants were interviewed within six-months of diagnosis, therefore follow-up interviews or interviews with participants further from diagnosis may have yielded additional experiences.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of more people with glioma may have provided a greater diversity of views. However, recruiting people with glioma was challenging, partly due to the effects of the COVID-19 pandemic, and also reflects the small sample sizes seen in other studies with this patient group ( Kirkman et al, 2023 ). Most participants were interviewed within six-months of diagnosis, therefore follow-up interviews or interviews with participants further from diagnosis may have yielded additional experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Management of cognitive deficits in people with primary brain tumors may include cognitive rehabilitation and/or pharmacotherapy. For a comprehensive review, we direct the reader to a recently published systematic review of cognitive interventions for adults with brain tumors by Kirkman and colleagues [62]. Out of 35 studies included in their review, 9 included at least a proportion of participants with glioblastoma (ranging from 4.8% to 100% of the study sample).…”
Section: Cognitive Rehabilitationmentioning
confidence: 99%
“…Out of 35 studies included in their review, 9 included at least a proportion of participants with glioblastoma (ranging from 4.8% to 100% of the study sample). Kirkman et al [62] included both randomized and nonrandomized studies; 14 studies reported on a pharmacological intervention and 21 on a nonpharmacological intervention. Examples of pharmacological agents that were associated with positive effects on cognition included memantine (NMDA receptor antagonist), donepezil (cholinesterase inhibitor), methylphenidate (CNS stimulant), modafinil (wakefulness-promoting agent), ginkgo biloba, and shenqi fuzheng.…”
Section: Cognitive Rehabilitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently 35 randomised and nonrandomised studies were included in a systematic review aimed to describe interventions used to ameliorate or prevent cognitive impairments in adults with BT: a range of interventions were associated with positive effects on cognition, including pharmacological agents such as memantine, donepezil, methylphenidate, modafinil, ginkgo biloba and shenqi fuzheng, and nonpharmacological interventions such as general and cognitive rehabilitation, working memory training, Goal Management Training, aerobic exercise, virtual reality training combined with computer assisted cognitive rehabilitation, hyperbaric oxygen therapy and semantic strategy training. Study limitations were identified and suggestions to standardise methods and outcome measures and to reduce bias were provided for future research in the field [60 ▪▪ ].…”
Section: Text Of Reviewmentioning
confidence: 99%